2005
DOI: 10.1002/cncr.20949
|View full text |Cite
|
Sign up to set email alerts
|

Postprostatectomy adjuvant versus salvage radiotherapy

Abstract: BACKGROUNDRadiotherapy (RT) has been used with success after radical retropubic prostatectomy (RRP), both in the adjuvant and salvage settings. The purpose of the current investigation was to systematically compare adjuvant versus salvage RT in a manner that incorporates both treatment efficacy and complications.METHODSA literature review was performed of reports of post‐RRP salvage and adjuvant RT, and 12 trials comprising 1060 patients met the appropriate inclusion criteria. The biochemical failure‐free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is also questionable whether adjuvant radiotherapy, systematically given to high-risk patients with no known recurrence, is a better cost-effective option than salvage treatment given to relapsing patients. From a clinical point of view, the superiority of one approach over the other will necessarily imply minimizing side effects [25]. The recently updated results of the EORTC 22911 trial presented at ESTRO 29 (Barcelona) and at ASTRO 2010 did not show any overall or metastasis-free survival benefit of adjuvant radiotherapy, possibly due to the use of early salvage therapy in the control arm.…”
Section: Discussionmentioning
confidence: 99%
“…It is also questionable whether adjuvant radiotherapy, systematically given to high-risk patients with no known recurrence, is a better cost-effective option than salvage treatment given to relapsing patients. From a clinical point of view, the superiority of one approach over the other will necessarily imply minimizing side effects [25]. The recently updated results of the EORTC 22911 trial presented at ESTRO 29 (Barcelona) and at ASTRO 2010 did not show any overall or metastasis-free survival benefit of adjuvant radiotherapy, possibly due to the use of early salvage therapy in the control arm.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] In one study, adjuvant RT was only found to be beneficial over salvage RT if the side effects were negligible, emphasizing the importance of side effects on treatment timing. 18 In addition, long-term follow-up from the European Organization for Research and Treatment of Cancer (EORTC) trial 22911 has shown that clinical progression-free survival rates previously reported with adjuvant RT were no longer clinically significant; moreover, in patients over 70, adjuvant RT had a detrimental effect on progression-free and overall survival. 2 The decision to treat with adjuvant or salvage RT is perhaps more controversial than ever and should include patient preference, demographics, pathologic features and risk of complications.…”
Section: Complications Of Radiotherapy After Prostatectomymentioning
confidence: 99%